A case of generalized tonic seizures related to acute myocarditis - Jeong-Hwan Yang; Jae Yoon Na; Jinseok Lee; Da-Eun Kim; Jinyoung Song; I-Seok Kang; Hyeryun Yeh (Pediatric Emergency Medicine Journal, 2020)
It is challenging to clinically distinguish between convulsive syncope and true seizure. We describe a 7-year-old girl presenting with generalized tonic seizure caused by acquired complete atrioventricular block related to acute myocarditis. After hospitalization following 6 episodes of new-onset fever with seizure, she had a short episode of abrupt complete atrioventricular block followed by another generalized tonic seizure. The concentrations of cardiac enzymes were elevated, and her echocardiogram showed a decreased left ventricular function. This case underlines the necessity of cardiac investigations in children with convulsive syncope.